Plants utilized as medicines by residents of Quilombo da Fazenda, Núcleo Picinguaba, Ubatuba, São Paulo, Brazil: A participatory survey. (15th November 2019) - Yazbek, P.B.; Matta, P.; Passero, L.F.; Santos, G.dos; Braga, S.; Assunção, L.; Sauini, T.; Cassas, F.; Garcia, R.J.F.; Honda, S.; Barreto, E.H.P.; Rodrigues, E.
Abstract: Ethnopharmacological relevance: Participatory research can help to broaden the understanding of medical systems and beliefs of traditional communities. An ethnopharmacological survey in collaboration with local people focused on plants used in quilombos located in Southeast Region in Brazil identified cultural factors that influence plant and recipe choice. Aim of the study: To investigate the factors related to the therapeutic efficiency of medicinal plants from the perspective of Quilombo da Fazenda residents. Materials and methods: University researchers collaborated with community residents for both aims and methods of the study. The local partners were trained in the gathering of ethnopharmacological data and then selected and interviewed the residents considered experts on the use of medicinal plants. Data on the use of each species were supported by voucher specimens collected by the local partners and university researchers. Participant observations and field diaries by the university researchers supplemented the data. Results: Eight interviewees mentioned 92 medicinal species with 60 therapeutic uses, applied in 208 recipes or remedies. Asteraceae (13 species), Lamiaceae (5) and Urticaceae (5) contributed most medicinal plant species. Of the 12 etic categories of use, the circulatory system category had the highest number of plants mentioned. Decoction was the most commonly used preparation method (66.8%), and most remedies were administered orally (76.4%). Eighty-six recipes included more than one plant species and/or the addition of other components, such as sugar, salt or animal products. Several cultural factors influence medicinal plant use. Popular beliefs on the quality of blood or the humoral properties of plants and illnesses, characteristics of the plants and other factors determine which plant is used and why. Conclusions: The participatory method identified a large number of factors that influence medicinal plant use: the patient's blood type ; the condition of the plant and the disease (hot-cold system); the route of administration and dosage; the preventive uses of the plants; and the influence of other factors, such as the sun, the moon and dew. The participatory approach is useful for gaining insight on the decision processes of medicinal plant use in traditional societies, and also for those communities wanting to document their knowledge with or without the participation of the academy. Graphical abstract: Image 1